Can Green Monetary Policy Drive Sustainable Growth? An SVAR Analysis of Bank Indonesia’s Green Policy Instruments - Kurniasih Christina, Elizabeth; Rusiadi; Nazliana Nasution, Lia; Ariani, Farida; Frananda, Santhos (International Conference Epicentrum of Economic Global Framework, 2026)
This study evaluates the effectiveness of Green Monetary Policy (GMP) in influencing Indonesia’s macro-financial dynamics to support sustainable growth. Using quarterly data from 2012Q1 to 2024Q4, this study models the transmission channels through a Structural Vector Autoregressive (SVAR) approach. The identification strategy utilized is a hybrid method incorporating sign restrictions and an external instrument-based proxy variable to accurately isolate structural shocks. Impulse response results indicate that a positive shock to green credit persistently increases the output gap and credit distribution, while inflationary pressures (greenflation) remain contained and transitory. Furthermore, financial system stability (FSI) is shown to improve over the medium horizon due to the banking portfolio shifting towards low-carbon assets. In conclusion, a well-calibrated GMP can spur green economic growth without compromising the central bank’s mandate for price stability. These findings imply the importance of strengthening targeted instruments, such as the Green Refinancing Window (GRW) and climate-adjusted collateral frameworks, within Bank Indonesia’s macroprudential and monetary operations.